2016
DOI: 10.4236/ojmm.2016.62010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of <i>Candida</i> Species and Molecular Typing of <i>C. albicans</i> Isolates in a Mexico City Tertiary Care Hospital from 2011 to 2013

Abstract: The incidence of yeast infections has increased significantly over the past few years, constituting a leading cause of morbidity and mortality among hospitalised patients. The rapid identification of candidiasis is important for the clinical management of patients and to facilitate tracing the sources of infections in hospitalized patients. Here, we report a retrospective, single-centre study of Candida spp. distribution and antifungal susceptibility from January 2011 to May 2013 at a hospital in México City, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
1
0
2
Order By: Relevance
“…Jamur kemudian berkolonisasi pada berbagai bagian tubuh terutama pada rongga mulut, usus, vagina dan menjadi komensal (Miranda et al 2009). Hasil indetifikasi molekuler menunjukkan C. albicans merupakan jenis yang ditemukan paling banyak pada tubuh manusia (73 %), diikuti C. tropicalis (15.0%), C. glabrata, (3.6%), dan C. parapsilosis (5.4% (Guerrero et al, 2016) Jamur Candida memiliki faktor adhesi yang membantu kolonisasi pada berbagai bagian tubuh tersebut dan juga berperan dalam patogenesis jamur. Berbagai molekul protein dapat disekresikan ke permukaan sel dan membantu pelekatan Candida para sel mukosa seperti protein famili Als, Hwp1, dan Eap1.…”
Section: Analisis Dataunclassified
“…Jamur kemudian berkolonisasi pada berbagai bagian tubuh terutama pada rongga mulut, usus, vagina dan menjadi komensal (Miranda et al 2009). Hasil indetifikasi molekuler menunjukkan C. albicans merupakan jenis yang ditemukan paling banyak pada tubuh manusia (73 %), diikuti C. tropicalis (15.0%), C. glabrata, (3.6%), dan C. parapsilosis (5.4% (Guerrero et al, 2016) Jamur Candida memiliki faktor adhesi yang membantu kolonisasi pada berbagai bagian tubuh tersebut dan juga berperan dalam patogenesis jamur. Berbagai molekul protein dapat disekresikan ke permukaan sel dan membantu pelekatan Candida para sel mukosa seperti protein famili Als, Hwp1, dan Eap1.…”
Section: Analisis Dataunclassified
“…In addition, detection of microsatellites also represents a reliable method for molecular typing and genetic analysis of Candida. A recent Candida distribution study conducted in a hospital, reported a clonal population including 62 identified genotypes among the tested isolates [25]. Beyond that, multilocus sequence typing (MLST) is another valuable method to understand the epidemiology of systemic Candida infections [2].…”
Section: Candida Albicansmentioning
confidence: 99%
“…Embora presente de maneira comensal no trato digestivo e, sobretudo, na cavidade oral, alguns estudos mostraram que a colonização oral assintomática pode levar à lesão oral ou tornar-se uma fonte de infecções disseminadas (Lockhart et al, 1999;Vargas et al, 2002;Fidel et al, 2006). As infecções sistêmicas provocadas pela Candida possuem uma taxa de mortalidade de 40% (Guerrero et al, 2016).…”
Section: Aspectos Gerais Das Espécies De Candidaunclassified